Effect of Regulating Channels and Activating Collateral Lotions on Quality of Life and Fatigue Symptoms of Patients with Post-stroke Fatigue - Leying ZHU; Qinling XU; Ruihuan PAN; Jing YANG; Mujia LI; Yinying PENG; Xiuhua ZHANG (康复学报)
Objective:To explore the effect of Regulating channels and activating collateral lotions on the quality of life and fatigue symptoms of patients with post-stroke fatigue(PSF).Methods:A retrospective analysis of 100 patients with post-stroke fatigue who were admitted to the Rehabilitation Department of Guangdong Provincial Hospital of Chinese Medicine from October 2014 to October 2016 and met the inclusion criteria of this study were divided into the treatment group and control group(50 cases in each group)according to the random number table method. The control group was treated with routine nursing care and comprehensive rehabilitation training, while the treatment group was additionally treated with Regulating channels and activating collateral lotions, and each group was observed for two weeks. Before and after treatment, the fatigue severity scale(FSS), the multidimensional fatigue inventory-20(MFI-20)and the energy score of the stroke-specific quality of life(SS-QOL-E)were used to assess the degree of fatigue and the improvement in quality of life.Results:After the treatment, the FSS score and MFI-20 score of the two groups were significantly lower, while SS-QOL-E score was significantly higher than that of before the treatment(P<0.05).After the treatment, the FSS score and MFI-20 score of the treatment group were significantly lower, and the SS-QOL-E score was significantly higher than that of the control group(P<0.05).Conclusion:On the basis of comprehensive rehabilitation training combined with routine nursing, supplemented with Regulating channels and activating collateral lotions can effectively alleviate the symptoms of fatigue after stroke and improve the quality of life, and the curative effect is better than that of comprehensive rehabilitation training combined with routine nursing.